ELECTRONIC EDUCATIONAL RESOURCES AS MEANS A SYSTEM OF TRANSMISSION OF EDUCATIONAL MATERIALS - Fakhriddin Zokir ugli Khasanov; Doniyor Erkin ugli Mirzoyev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In the current era of globalization, real-time teaching through the Internet is considered one of the most rapidly developing methods of education. The e-learning system makes it possible to teach and receive education at a voluntary distance without any barriers. According to the expert, the learning efficiency is higher in the real-time distance education system compared to the traditional education system.